1. а)Х_1=2 1/2
Х_2=-1 1/2
б)Х_1=9
Х-2=-9
Объяснение:
2.
а)4х^2-4х-15=0
a=4 b=-4 c=-15
D =b^2-4ac
D=4^2-4×4×(-15)=16-240=256=16^2>0
X_1=-(-4)+16/2×4=20/8=5/2=2 1/2
X_2=-(-4)-16/2×4=-12/8=-3/2=-1 1/2
D/4=(4/2)^2-4×(-15)=2^2+60=64=8^2>0
X_1=(2+8)/4=10/4=5/2=2 1/2
X_2=(2-8)/4=-6/4=-3/2=-1/1/2
ответ: Х_1=2 1/2
Х_2=-1 1/2
б)Х^2-9^2=0
Применяем формулу разности квадратов:
(Х-9)(Х+9)=0
Х-9=0
Х_1=9
Х+9=0
Х_2=-9
ответ: Х_1=9
Х_2=-9
1.
Упростить:
=(2×(3×9)^1/2-(3×100)^1/2+(2×9)^1/2)×
×(3^1/2)+(24)^1/2=(2×3×(3^1/2)-10×(3^1/2)+
+3×(2^1/2))×(3^1/2)=
=6×3-10×3+3×(6^1/2)+(4×6)^1/2=
=18-30+3×(6^1/2)+2×(6^1/2)=
=-12+5(6^1/2)
ответ: -12+5(6^1/2)
а)sin 5п/4=sin(π-π/4)=sin π/4=√2/2
б)tg 7п/6=tg(π+π/6)=tg π/6=√3/3
в)cos п/6 - ctg π/4=√3/2-1г)tg 3п/4 x cos 3п/4+сtg(-п/6) х sin п/6=sin 3π/4/cos 3π/4*cos 3π/4-cosπ/6/sinπ/6*sinπ/6=sin 3π/4-cos π/6=sin(π-π/4)-cosπ/6=sinπ/4-cosπ/6=√2/2-√3/2
д)sin 510-sin270 ctg270=sin (2π+π-30)-sin 270*cos270/sin270=sin30-cos(2π-90)=1/2-1=-0.5
2)Упростите выражение
сos^2 - sin^2t/tg(-t)ctgt=cos²t-sin²t/(-tg t)*ctg t=cos²t+sin²t=1
3)Решите уравнение:
a)sint=1/2
t=x = (-1)^k П/6 + Пk, k∈Z;
б)sin(п/2 + t)=- корень из 3/2
cos t=-√3/2
t=+-5π/6+2πk, k∈Z
4)Известно,что ctg(t-п)=-3/4 и п/2 п/2<t<п
ctg(-(π-t))=-ctg(π-t)=ctg t
ctg t=cos t/sin t=-3/4
4cost=-3sint
4cost=-3√(1-cos²t)
16cos²t=9(1-cos²t)
16cos²t=9-9cos²t
25cos²t=9
cos²t=9/25
cost=+-√(9/25)=+-3/5, cost<0 (t∈(π/2; π)
cost=-3/5=-0.6
sin t=cos t/ctg t=-0.6/(-3/4)=0.2*4=0.8
Найдите:
a)cos(3п/2 - t)=-sint=-0.8
б)cos(п + t)=-cost=-(-0.6)=0.6
5)Расположите в порядке возростания:
a=cos6
b=cos7
c=sin6=sin (π/2-(π/2-6))=cos (90-6)=cos 84
d=sin 4=sin (π/2-(π/2-4))=cos (90-4)=cos 86
Поскольку cos убывает на промежутке [0; π/2], то
cos 86<cos 84<cos7<cos6
d<c<b<a